Igniting research competency: Empowering pre-service teachers through communities of practice plus lesson study - Kanyarat Cojorn; Chaweewan Seesom (LPMPP Universitas Negeri Yogyakarta, 2026)
The establishment of Communities of Practice (CoP) is recognized as a powerful means of fostering collaborative learning. CoP provides members with a platform to collectively develop their potential, exchange ideas, and engage in creative problem-solving. Similarly, LS is a well-established instructional improvement process that supports the holistic development of learners’ knowledge and skills. In this study, a learning approach that integrates CoP principles with the LS framework was utilized to create a shared learning space for pre-service science teachers. The primary aim is to investigate the implementation and effectiveness of activities that combine CoP and LS approaches in enhancing research competence among pre-service teachers. Specifically, the study evaluates the development of three key components of research competence: research knowledge, research skills, and research attributes. The findings indicate that the integrated use of CoP and LS significantly enhanced the research competencies of pre-service teachers. Participants demonstrated the ability to adjust their strategies to align with the expectations of the CoP. Additionally, they exhibited improved self-regulation, enabling them to independently design, plan, and complete research projects. Increased self-efficacy was also observed, as the pre-service teachers reported greater confidence in their research competency.